2001
DOI: 10.1002/1529-0131(200101)44:1<41::aid-anr6>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of anti-citrulline-containing peptide antibody by B lymphocytes in rheumatoid arthritis

Abstract: Objective To understand the regulation of anti–citrulline‐containing peptide antibody (anti‐CCP) production in rheumatoid arthritis (RA), production of anti‐CCP by B cells derived from peripheral blood (PB), bone marrow (BM), and synovial fluid (SF) was examined. Methods Purified PB and SF B cells were isolated by negative selection and then cultured in the absence or presence of L–CD40 ligand cells and interleukin‐10 or anti‐CD3–activated T cells. Total IgM and IgM–anti‐CCP were detected after 14 days of cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
76
2
10

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(89 citation statements)
references
References 24 publications
1
76
2
10
Order By: Relevance
“…Previous data indicated that not all in vivo or in vitro substrates reactive with ACPA are pathophysiologically relevant, as illustrated by deiminated filaggrin, and that the relevant antigenic target(s) are probably present in the inflamed joint (14,47). Therefore, the present study addressed the pathophysiologic relevance of synovial targets of ACPA by directly analyzing human synovial tissue and paired serum and SF samples.…”
Section: Discussionmentioning
confidence: 97%
“…Previous data indicated that not all in vivo or in vitro substrates reactive with ACPA are pathophysiologically relevant, as illustrated by deiminated filaggrin, and that the relevant antigenic target(s) are probably present in the inflamed joint (14,47). Therefore, the present study addressed the pathophysiologic relevance of synovial targets of ACPA by directly analyzing human synovial tissue and paired serum and SF samples.…”
Section: Discussionmentioning
confidence: 97%
“…This structure contains proliferating fibroblast-like synoviocytes (FLS) and dividing T and B lymphocytes (2). The latter cells produce antibodies with specificity for the Fc region of IgG (3) or antibodies to cyclic citrullinated peptides (4). They also release proinflammatory cytokines, such as tumor necrosis factor ␣ (TNF␣) (5) and interleukin-6 (IL-6) (6).…”
mentioning
confidence: 99%
“…The most prevalent autoantibody reactivity in RA is RF, with IgG-RF being particularly implicated in the formation of small immune complexes (2,22), but a significant proportion of patients also have raised levels of antibodies to cyclic citrullinated peptides (anti-CCP) (23) and to proteins such as the immunoglobulin heavy-chain binding protein (anti-BiP) (24). In the absence of T cell responses to IgG, there is particular interest in the possible roles of T cell responses to these other antigens and their interrelationships with RF B cells.…”
mentioning
confidence: 99%